Livestock-associated methicillin-resistant Staphylococcus aureus (LA-MRSA) spa type t127, Sequence Type (ST)1, quickly spreads and persists among young pigs. Issue 3 (27th June 2019) - Merialdi, Giuseppe; Feltrin, Fabiola; Gaetarelli, Barbara; Lombardi, Guerino; Iurescia, Manuela; Alba, Patricia; Luppi, Andrea; Martinelli, Nicola; Ramini, Mattia; Carfora, Virginia; Franco, Alessia; Battisti, Antonio
ABSTRACT: Livestock-associated methicillin-resistant Staphylococcus aureus (LA-MRSA) clones other than Clonal Complex (CC)398, as CC1, have been isolated in pigs in some countries, and appeared to be prevalent in Italy. The aim of this study was to evaluate the capability of Sequence Type (ST)1, CC1, LA-MRSA clone to colonize and to be transmitted among piglets. Eighteen caesarean-derived/colostrum-deprived piglets of 35 days of age were assigned randomly to three groups: four seeder piglets were contaminated with a spa type t127, ST1, SCC mec V, MRSA (Group A), 10 MRSA-negative piglets were exposed to Group A after 2 days post-contamination, dpc (Group B) and 4 piglets were used as control group (Group C). Piglets were evaluated until 44 dpc (Group A) or at 42 days post-exposure, dpe (Group B) and then euthanized and necropsied. All nasal and skin cultures of Group A resulted MRSA-positive throughout the experiment starting from two dpc, while Group C tested always MRSA-negative. At first sampling, all Group B piglets became positive and remained positive throughout the experiment. This is the first colonization/transmission study with a CC1 LA-MRSA in pigs. The results add further knowledge on the ability of CC1 LA-MRSA to colonize pigs, and on colonization/transmission patterns, both suggesting good host adaptation. Abstract : This is the first colonization/transmission study performed in piglets with a Livestock-associated methicillin-resistant Staphylococcus aureus (LA-MRSA), Clonal Complex (CC)1, rapidly transmitted to negative contact-piglets, which remained all positive throughout the experiment.